2006
DOI: 10.1152/jn.00597.2005
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Background Colors on the Tuning of Color-Selective Cells in Monkey Area V4

Abstract: . When objects are viewed in different illuminants, their color does not change or changes little in spite of significant changes in the wavelength composition of the light reflected from them. In previous studies, we have addressed the physiology underlying this color constancy by recording from cells in areas V1, V2, and V4 of the anesthetized monkey. Truly color-coded cells, ones that respond to a patch of a given color irrespective of the wavelength composition of the light reflected from it, were only fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 41 publications
3
43
1
Order By: Relevance
“…Accordingly, we did not find significant stimulus correlations between VEPs and spiking activity. The lack of color sensitivity at the population level in V4 seems to be at odds with previous studies recording single unit activity that illustrate the importance of V4 in color processing (Zeki, 1980(Zeki, , 1983aWild et al, 1985;Walsh et al, 1993;Kusunoki et al, 2006;Stoughton and Conway, 2008;Conway and Tsao, 2009). Instead, our findings might rather be consistent with studies questioning a specific role of V4 neurons in color processing (Schein et al, 1982;Tootell et al, 2004).…”
Section: Discussioncontrasting
confidence: 98%
“…Accordingly, we did not find significant stimulus correlations between VEPs and spiking activity. The lack of color sensitivity at the population level in V4 seems to be at odds with previous studies recording single unit activity that illustrate the importance of V4 in color processing (Zeki, 1980(Zeki, , 1983aWild et al, 1985;Walsh et al, 1993;Kusunoki et al, 2006;Stoughton and Conway, 2008;Conway and Tsao, 2009). Instead, our findings might rather be consistent with studies questioning a specific role of V4 neurons in color processing (Schein et al, 1982;Tootell et al, 2004).…”
Section: Discussioncontrasting
confidence: 98%
“…Past studies in area V4 have demonstrated selectivity for both stimulus form (Desimone and Schein 1987;Gallant et al 1993;Kobatake and Tanaka 1994;Connor 1999, 2001) and color (Bushnell et al 2011b;Conway et al 2007;Kotake et al 2009;Kusunoki et al 2006;Schein and Desimone 1990;Zeki 1973). However, because characterizations of tuning have typically been performed along the dimension of interest (shape or color) while holding the other (color or shape) constant, past V4 results do not reveal whether selectivity for form and color interact at the single-neuron level, i.e., whether shape preferences are the same regardless of the color of the stimulus.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, the color map may incorporate knowledge or qualities that are intrinsic constructs, such as color constancy (Schein and Desimone, 1990), the percept of which cannot be simply predicted from the physical properties of the light (McCann et al, 1976;Land, 1977;Lotto and Purves, 2002;Kusunoki et al, 2006). Thus, some aspects of its recorded activity may not only represent colors in the external world but also reflect correlations to internal factors, arising from the complex dynamics of the underlying cortical circuits (Harris, 2005).…”
Section: Requirements For Distributed Combinatorial Representationsmentioning
confidence: 99%